Trends in the Incidence and Survival Rates of Primary Ovarian Clear Cell Carcinoma Compared to Ovarian Serous Carcinoma in Korea - Kim, Se Ik; Ha, Hyeong In; Eoh, Kyung Jin; Lim, Jiwon; Won, Young-Joo; Lim, Myong Cheol (Frontiers in Oncology, 2022)
Objective: To compare the incidence and survival rates of primary ovarian clear cell carcinoma (OCCC) and ovarian serous carcinoma (OSC) from a nationwide collected database. Methods: We extracted information of patients with primary OCCC and OSC from the Korea Central Cancer Registry recorded between 1999 and 2018, including age at diagnosis and the Surveillance, Epidemiology, and End Results summary stage. Age-standardized rates (ASRs) and annual percent changes (APCs) were calculated. Baseline characteristics and overall survival (OS) were compared between the OCCC and OSC groups. Results: Overall, the incidence rate of primary OCCC increased markedly from 1999 (ASR, 0.16/100,000) to 2018 (0.76/100,000) (APC, 7.85%; P<0.0001). Patients with OCCC were significantly younger and had early-stage disease more frequently than those with OSC. Patients diagnosed with OCCC before the age of 50 showed better OS than those diagnosed after the age of 50 (P=0.0048). The 5-year OS of the OCCC group did not differ by study period [73.4% (1999–2008) vs. 75.4% (2009–2018), P=0.3187], whereas the 5-year OS of the OSC group improved from 54.4% to 58% (P=0.0003). Conclusions: Our nationwide registry-based study demonstrated that the incidence of OCCC in Korea increased significantly from 1999 to 2018. Early-stage OCCC had a relatively good prognosis, but advanced-stage OCCC had a worse OS than advanced-stage OSC. Therefore, the development of optimal treatment strategies for OCCC is warranted.